ITest: A novel online testing system based on the WeChat platform. Issue 4 (10th June 2019) - Xu, Jia; Wang, Junbin; Wang, Xiaoxin; Lv, Pin
Abstract: Timely feedback is important for both teachers and students in teaching and learning practice. Teachers rely on feedback from students to gain a better understanding of their learning effects. Students also need feedback to identify gaps in their knowledge. Conducting in‐class tests is considered an effective way to obtain such feedback. However, traditional testing methods are inflexible and inefficient. In this paper, we introduce iTest, a novel online testing system developed on the popular WeChat platform. With the help of iTest, the teacher organizes an in‐class test conveniently, and the students take the test with their smartphones regardless of which operating systems the smartphones use. When the student answers questions in a test, abundant behavior data for the student are collected. According to the analysis of the behavior data and the testing results, the teacher gains a deeper insight into the learning effect for each student. A weighted knowledge graph is also constructed for each student by virtue of the prerequisite relationships among the knowledge points and the behavior data. On the basis of the weighted knowledge graph, iTest recommends personalized exercises in an appropriate order to each student after the test, which helps to improve the learning effect. Teaching practice in five courses verifies that iTest is effective and efficient in promoting teaching and learning. Both teachers and students have high praise for iTest.